Ground states and phase transition of the λ model on the Cayley tree - Mukhamedov, Farrukh; Jamil, Hakim; Pah, Chin Hee (Pleiades Publishing, Ltd., 2018)
We consider the λ model, a generalization of the Potts model, with spin values {1, 2, 3} on the order-two Cayley tree. We describe the model ground states and prove that translation-invariant Gibb measures exist, which means that a phase transition exists. We establish that two-periodic Gibbs measures exist.